Cross-cultural adaptation of evidence-based practice measure among Hong Kong healthcare providers - Fadi M. Al Zoubi; André Bussières; Jason P. Y. Cheung; Eric Chun-Pu Chu; Hammoda Abu-Odah; Arnold Y. L. Wong; Aliki Thomas (PLoS ONE, 2026)
Objective This study aimed to adapt and validate an Evidence-Based Practice (EBP) tool for healthcare providers in Hong Kong, addressing the need for reliable and culturally relevant tools. Methods The original EBP measure, developed for recent Canadian physiotherapy and occupational therapy graduates, was systematically adapted for use by healthcare providers in Hong Kong following established cross-cultural adaptation guidelines. The adaptation process consisted of two phases: Phase I involved forward and backward translation, expert panel review, and cognitive debriefing interviews with a purposive sample of 36 healthcare providers to ensure linguistic and cultural relevance. In Phase II, the finalized instrument was administered to a convenience sample of 248 registered healthcare providers in Hong Kong. The structure of the adapted instrument remained consistent with the original, comprising two models encompassing six constructs: (1) a formative model (use of EBP and EBP activities) and (2) a reflective model (knowledge, self-efficacy, attitudes, and resources). Construct validity was assessed using the Rasch model, internal consistency reliability was evaluated with the Person Separation Index (PSI), and differential item functioning (DIF) was examined. Results The formative model only required linguistic modifications. The Rasch model was applied to the reflective component. For knowledge, 45% (5/11) items fit the Rasch model with a chi-square fit statistic (χ² = 17.90, p = 0.268; PSI = 0.84). For self-efficacy, 89% (8/9) items fit the Rasch model with χ² = 26.48, p = 0.33; PSI = 0.93. The attitudes construct was divided into positively and negatively worded subscales due to multidimensionality. The resources construct showed a good fit with χ² = 26.60, p = 0.49; PSI = 0.84. DIF was not observed in the final measures. Conclusions The adapted EBP measure demonstrated evidence of construct validity and internal consistency reliability among healthcare providers in Hong Kong. However, further research is needed to assess additional aspects of validity, such as test–retest reliability and responsiveness, as well as to evaluate its applicability in broader healthcare settings.